Urgensi Pembelajaran Bahasa Arab dalam Pendidikan Islam - Nasution, Novita Sari; Lubis, Lahmuddin (Jurnal Simki Pedagogia, 2023)
This study aims to obtain information about the Urgency of Learning Arabic in Islamic Education. This research is a library research (Library Research). The library method is a suitable method in this research. Because in this case library sources such as books and journals both nationally and internationally will be used to collect various data relating to instilling the values of monotheism in learning Arabic. The results of this study indicate that there is an urgency to learn Arabic in the realm of Islamic education when viewed from the perspective of human life, structurally related to cultural tools. The final goal of Islamic education is to become part of the actualization of the will of Islamic teachings with the mission of starting to prosper mankind as essentially servants of God Almighty, Allah SWT, both physically and spiritually, in this world and in the hereafter with the basis that we are holy Al-Qur'an also Hadith.